Información sobre el uso de animales de laboratorio indicada en artículos científicos - Granados-Zúñiga, Jorge (Universidad de Costa Rica, 1997)
A sample of 15 Costa Rica scientific paper published since 1985 reported only 49% of the necessary information about laboratory animals of experimental conditions, sligth better than in the rest of latin America